Difference in Satisfaction Levels of National Health Insurance Patients at Four Types of First Level Health Facilities - Ni Made Widiastuti; Ni Made Sri Nopiyani; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2015)
Backgrounds and purpose: The road map of the National Health Insurance Scheme (JKN) aims to ensure that 75% of patients are satisfied with the quality of health facilities. This study was designed to determine differences in patients’ satisfaction in general, as well as at each individual first-level health facility (FKTP) and based on dimensions of quality. Methods: Study was a cross-sectional sample survey with the respondents of 148 JKN patients selected consecutively from 4 types of FKTP. A total of 4 health centers, 3 government clinics, 4 private clinics and 4 general practitioners randomly selected from 11 health centers, 7 government clinics, 13 private clinics and 70 general practitioners in the city of Denpasar. Data were collected through interviews over March-April 2015 in each health facility using questionnaires by trained interviewers. Data were analyzed by univariate, bivariate and multivariate. Results: A total of 69,59% of JKN patients said that they were satisfied with the quality of FKTP services. This figure was lower than the target of JKN i.e. 75%. The highest satisfaction (90,00%) was in the general practitioners while lowest was in the private clinics (47,46%). Based on the dimensions of quality, JKN patients’ satisfaction in the four FKTPs was significantly different (p=0,008) in physical and empathic dimensions (p=0,013). In the multivariate analysis, variables found related to the satisfaction of the respondents were the FKTP of general practitioners (adjusted PR=1,91; 95%CI: 1,05-3,47) and health centers (adjusted PR=1,76; 95%CI: 1,04-2,97). Conclusion: In general, the patients’ satisfaction rate was still lower than the target of JKN and when viewed per care facilities, the highest satisfaction was found in FKTP of general practitioners and health centers.